Arab Aid on the Rise 2011-2016 - Rouis, Mustapha; Shomakhmadova, Olga (World Bank, Washington, DC, 2018)
Arab donors continue to be responsive to the needs of developing countries. Gulf countries, notably Kuwait, Saudi Arabia, and the United Arab Emirates; and Arab financial institutions have increased their financial assistance overtime, during the global financial crisis and in the aftermath of the Arab Spring for Arab countries in transition.